Malthusianism, Capitalist Agriculture, and the Fate of Peasants in the Making of the Modern World Food System - Eric B. Ross (Review of Radical Political Economics 2003; 35; 437, 2003)
This article describes the role of Malthusian thinking as a rationale for the commercial development of global agriculture at the expense of peasant-livelihood security. Focusing on the impact of the cold war, in an era of peasant insurgency, it explores how the Green Revolution reflected and reinforced the West's conviction that technological innovation, rather than more equitable systems of production, should resolve the problem of world food security said to be due to overpopulation.